(untitled) (MAUSAM, 1990)
A global description of the monsoon phenomenon as deduced from the analy5is of the comprehensive FGGE/MONEX data sets is presented. The Indian summer monsoon is one of the two components along with. The East Asia monsoon of the Asian summer monsoon, which influences the 1arge-scale dynamics of the entire tropical belt. The monsoon circulation can be described within the theoretical framework of equatorially trapped waves in response to the 1ocalized release of heat. The 30-50 day oscillation is presented because the demonstration of Its influence on the activity of the summer monsoon at sub-seasonal scales is one of the major salient results obtained during MONEX.